2016
DOI: 10.5863/1551-6776-21.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Measuring Devices Packaged With Prescription Oral Liquid Medications

Abstract: Packaging of prescription oral-liquid medications is inconsistent and leaves room for vast variability in patient or parent administration practices. In the future, patterns of actual dispensing practices among pharmacies and pharmacists would help determine the true incidence of dispensing of measuring devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(13 reference statements)
1
4
0
Order By: Relevance
“…In an attempt to determine the availability and accuracy of dosing devices, Bayor et al [ 6 ] found that dosing devices were not packaged with 46% and 97% of orthodox and herbal oral liquid medicines, respectively, on the Ghanaian market. A similar trend was found in the research by Johnson and Meyers [ 7 ] where it was revealed that only 12.8% of 382 liquid prescription medications were packaged with a dosing device. Consequently, caregivers are compelled to use devices such as household spoons to deliver required medication doses.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…In an attempt to determine the availability and accuracy of dosing devices, Bayor et al [ 6 ] found that dosing devices were not packaged with 46% and 97% of orthodox and herbal oral liquid medicines, respectively, on the Ghanaian market. A similar trend was found in the research by Johnson and Meyers [ 7 ] where it was revealed that only 12.8% of 382 liquid prescription medications were packaged with a dosing device. Consequently, caregivers are compelled to use devices such as household spoons to deliver required medication doses.…”
Section: Introductionsupporting
confidence: 84%
“…A study assessing compliance of OTC liquid products with these guidelines showed a glaring need for improvements in dosing devices for these products, with 98.6% of products having a discrepancy between the dose on the label and the measuring device in the package [ 10 ]. There are reports of adherence to the recommendations [ 14 ]; however, dosing device availability remains woefully inadequate as it is still not a standard practice for dosing tools to be provided in the clinical or community pharmacy setting [ 7 , 15 ]. Further, the provision of dosing devices for prescription medications is inadequate compared to OTC medications.…”
Section: Introductionmentioning
confidence: 99%
“…For the last 15 years or so, there is a call to make this requirement mandatory for all liquid medicines (OTC and prescription) [50,51]. Studies have reported that provision of a suitably calibrated measuring device is now commonly seen with OTC liquid medicines but not for all prescription medicines, even in developed countries [52,53].…”
Section: Administering the Right Dosementioning
confidence: 99%
“…Although measuring cups or calibrated droppers are now included with most over-the-counter pediatric liquid medications, there are currently no regulations requiring that DDDs, such as oral syringes or dosing spoons, be dispensed with liquid prescription medications and given instructions for their use. A recent study by Johnson and Meyers 6 reported variable dispensing practices for delivery devices in a chain community pharmacy for liquid prescription medications. To our knowledge, no other published studies have focused on local, regional, or national pharmacy practice patterns, which remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%